Lifelong learning and the Roma minority in western and southern Europe - Óhidy, Andrea; Forray, Katalin R. (Bingley, U.K. : Emerald Publishing Limited, 2019)
The achievement and success of Roma people in education is at a breaking point across Europe, severely limiting social mobility. Recent research has shown that Roma are the most underrepresented group in schools and other educational institutions. There are an array of policy measures and initiatives across Western and Southern Europe seeking to reverse this and to raise educational access and attainment of the Roma population.This book offers an in-depth exploration into the current educational climate and the impact of these policy measures for Roma people in seven Western and Southern European countries: Germany, Greece, Italy, Norway, Portugal, Spain and Sweden. This book seeks to raise awareness of this forgotten minority and to assess the policies implemented to integrate the Roma people into the education system. Written by experts across Western and Southern Europe and drawing on varied cultural perspectives, this work will help to address the severe lack of information and knowledge about the Roma people available in the public domain. This book will prove invaluable to those in the field of comparative education, educational leaders and practitioners in Western and Southern Europe and beyond.
Introduction: lifelong learning and the Roma minority in western and southern Europe / Katalin R. Forray and Andrea Óhidy -- Chapter 1. Bottom up, top down and human rights: Roma organizations, policy frameworks and european institutions / Natascha Hofmann -- Chapter 2. Dawn of learning! Sinti and Roma in Germany / Natascha Hofmann -- Chapter 3. Lifelong learning for Roma in European countries: the Greek case / Panagiota Gkofa -- Chapter 4. The education of Roma, Sinti and Caminanti children in Italy: pathways to school inclusion / Valeria Cavioni -- Chapter 5. The educational situation for Roma in Norway / Kari Hagatun -- Chapter 6. The Roma population in portugal: a changing picture / Pedro Calado, Liliana Moreira, Sónia Costa, Celeste Simões, Margarida Gaspar de Matos -- Chapter 7. Moving towards Roma inclusion in Spain through successful educational actions / Fernando Macías-Aranda, Teresa Sordé-Martí, Jelen Amador-López and Adriana Aubert-Simó -- Chapter 8. Roma in the educational system of Sweden: achievements after year 2000 and challenges for the future / Christina Rodell Olgaç -- Conclusion: Participation and success of European Roma in education and lifelong learning: common challenge, similar solutions and hitherto unsatisfactory results / Andrea Óhidy -- Index.
Includes index.
Print version record.
Keywords: Romanies -- Education -- Europe; Romanies -- Education (Continuing education) -- Europe; Education -- Educational Policy & Reform -- General; Adult education, continuous learning